Design, Synthesis, and Biological Evaluation of Pyrano[2,3-c]-pyrazole–Based RalA Inhibitors Against Hepatocellular Carcinoma - Wang, Yuting; He, Mingyao; Li, Xiang; Chai, Jinlong; Jiang, Qinglin; Peng, Cheng; He, Gu; Huang, Wei (Frontiers in Chemistry, 2021)
The activation of Ras small GTPases, including RalA and RalB, plays an important role in carcinogenesis, tumor progress, and metastasis. In the current study, we report the discovery of a series of 6-sulfonylamide-pyrano [2,3-c]-pyrazole derivatives as novel RalA inhibitors. ELISA-based biochemical assay results indicated that compounds 4k–4r suppressed RalA/B binding capacities to their substrates. Cellular proliferation assays indicated that these RalA inhibitors potently inhibited the proliferation of HCC cell lines, including HepG2, SMMC-7721, Hep3B, and Huh-7 cells. Among the evaluated compounds, 4p displayed good inhibitory capacities on RalA (IC50 = 0.22 μM) and HepG2 cells (IC50 = 2.28 μM). Overall, our results suggested that a novel small-molecule RalA inhibitor with a 6-sulfonylamide-pyrano [2, 3-c]-pyrazole scaffold suppressed autophagy and cell proliferation in hepatocellular carcinoma, and that it has potential for HCC-targeted therapy.